PROBLEMS AND PERSPECTIVES OF FRESH WATERS CONDITION PROGNOSIS ON INTAKE OF KRYVYJ RIG CITY - SHEVCHENKO, O.; SYZONENKO, V.; KOZYTSKYI, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The problem of contamination of waters from Kryvyj Rig water supply points is discussed. The contamination is spreaded through hydro system of Zheltaya River and Ingulets River, due to the filtration losses and upcasts from sludge ponds of uranium mine "Nova" in the Zhovti Vody settlement. The necessity of application of the already developed programm complex of operative analysis and forecast of credible changes of quality of water on water supply point of Kryvyj Rig is demonstrated.